University teachers’ conceptions of the university and the place of sustainability - Chaleta, E; Saraiva, M.; Sebastião, L.; Cid, M.; Dinis, A. M.; Leal, F.; Paulo Quaresma; Rato, L. (Sustainability, 2021)
In this phenomenographic qualitative research, the aim is to learn about the conceptions of university professors about the university. The study was carried out with 20 university professors: 10 from the School of Social Sciences and 10 from the School of Science and Technology of University of Évora with an average age of 54 years and over 20 years of professional activity. The data were collected through open questionnaires and then submitted to thematic and categorical content analysis. The conceptions of the university appear, in the voice of the teachers, centered on two main aspects. The first and more mentioned concerns the conception of the university as a space of production and diffusion of scientific knowledge, which refers to quality factors of higher education. The second brings out the conception of the university as a space of relationship with society together with underlying concerns for human development, cooperation, and the design of a more sustainable world.